Dynamic modelling for high pressure CO2 Absorption from Natural Gas - Isa, F. (Springer Verlag, 2017)
This paper reports the dynamic simulation model of high content CO2 from natural gas at elevated pressure. The common process of CO2 modelling are mostly reported in steady state condition at atmospheric pressure. However, disturbances such as startup, shut down, and temperature rise might occur during the absorption process. Therefore, the dynamic study has been conducted in this paper via equilibrium approach with some adjustments to observe the efficiency of CO2 removal at the top of the column. Input data for the simulation had been acquired from the pilot plant in Universiti Teknologi PETRONAS (UTP). Aspen Dynamic simulator is not able to support the rate based approach and therefore, several adjustments such as the number of stages and Murphree efficiency need to be imposed on the equilibrium stage model to produce similar result as the pilot plant and as well as rate based approach. The error percentage of CO2 removal observed between actual plant and simulation using equilibrium based approach is less than 5 with several adjustment implemented in the simulator. The results show that the equilibrium approach with some adjustments is able to replicate the pilot plant under dynamic conditions. In dynamic study, the lean solvent flowrate is varied to study the performance of CO2 removal and it is observed the higher solvent lean solvent flowrate improves the efficiency of CO2 removal. © Springer Nature Singapore Pte Ltd. 2017.